Contested suburban mobilities: towards a sustainable urbanism of justice and difference - Zhou, Shimeng, author (Colorado State University. Libraries, 2017)
Mainstream understandings of sustainability are dominated by post-political discourses that tend to favour technological solutions while overlooking social justice. This paper draws attention to the different and often uneven ways in which sustainable urban environments, and their associated practices of citizenship and mobility, are produced and contested. By combining critical approaches to sustainable urbanism, ecological citizenship and mobility with social practice theory, this paper highlights the social justice dimensions of 'green' transitions through the case of a cycling-promoting initiative within a sustainable regeneration project ('Sustainable Järva') in Järva, an ethnically diverse suburb outside Stockholm, Sweden. The results reveal divergent understandings of suburban regeneration and ecological citizenship among different groups, and the deeply political nature of cycling. In 'Sustainable Järva', the practices of ecological citizenship promoted have overlapped with norms and values linked to a 'Swedish' identity associated with environmental responsibility, familiarity with nature, and active outdoor mobility, thus normatively reproducing power structures of class and race in the public opinion on desired forms of ecological citizenship and mobility. The results challenge post-political understandings of 'sustainability', affirming that just transitions to sustainable futures that ensure both the 'green' and the 'just' require environmentally progressive ontologies of sustainability, urbanism, ecological citizenship and mobility, promoting ecologically sound transitions while accommodating difference, and addressing the joint environmental and social justice implications for diverse communities.
Presented at the Environmental justice in the Anthropocene symposium held on April 24-25, 2017 at the Lory Student Center, Colorado State University, Fort Collins Colorado. This symposium aims to bring together academics (faculty and graduate students), independent researchers, community and movement activists, and regulatory and policy practitioners from across disciplines, research areas, perspectives, and different countries. Our overarching goal is to build on several decades of EJ research and practice to address the seemingly intractable environmental and ecological problems of this unfolding era. How can we explore EJ amongst humans and between nature and humans, within and across generations, in an age when humans dominate the landscape? How can we better understand collective human dominance without obscuring continuing power differentials and inequities within and between human societies? What institutional and governance innovations can we adopt to address existing challenges and to promote just transitions and futures?
Keywords: sustainable urbanism; eco-city; suburban regeneration; ecological citizenship; gentrification; practice; cycling; difference; Sweden